A Square‐Planar Tetracoordinate Oxygen‐Containing Ti4O17 Cluster Stabilized by Two 1, 1′‐Ferrocenedicarboxylato Ligands1. Issue 35 (2nd July 2014) - Liu, Zhichang; Lei, Juying; Frasconi, Marco; Li, Xiaohu; Cao, Dennis; Zhu, Zhixue; Schneebeli, Severin T.; Schatz, George C.; Stoddart, J. Fraser
Abstract By introducing steric constraints into molecular compounds, it is possible to achieve atypical coordination geometries for the elements. Herein, we demonstrate that a titanium‐oxo cluster [{Ti4(μ4‐O)(μ2‐O)2}(OPri)6(fdc)2], which possesses a unique edge‐sharing Ti4O17 octahedron tetramer core, is stabilized by the constraints produced by two orthogonal 1, 1′‐ferrocenedicarboxylato (fdc) ligands. As a result, a square‐planar tetracoordinate oxygen (ptO) can be generated. The bonding pattern of this unusual anti‐van't Hoff/Le Bel oxygen, which has been probed by theoretical calculations, can be described by two horizontally σ‐bonded 2px and 2py orbitals along with one perpendicular nonbonded 2pz orbital. While the two ferrocene units are separated spatially by the ptO with an Fe⋅⋅⋅Fe separation of 10.4 Å, electronic communication between them still takes place as revealed by the cluster's two distinct one‐electron electrochemical oxidation processes.